When usage matters: time-of-use analysis of Cape Town's Day Zero drought response - M. J. Booysen (IWA Publishing, 2021)
Poor resource management and infrastructure limitations make the effects of drought worse for cities in developing countries. One way to alleviate the impact without large investments is targeted demand management. This has worked well in studies that focused on some of the recent droughts, including Cape Town's ‘Day Zero’ drought of 2016–2018. Many studies have measured demand response to a drought at a coarse time resolution, but few have measured it at an hourly resolution or compared weekday with weekend use. In this study we evaluated households' hourly time-of-use behaviour in response to the Cape Town drought at two prominent inflection points identified by previous studies: the announcement of the Critical Water Shortages Disaster Plan in October 2017 and the introduction of Level 6B restrictions in February 2018. The first major reduction was caused by residents reducing their usage by about a third in the early morning and evening hours on weekdays, and the second, even larger, reduction was achieved in the mid-morning hours on weekdays when home owners were not at home but ensured that domestic workers used water sparingly. HIGHLIGHTS Demand side management works better than supply side in a developing country.; Cape Town's severe 2016-2018 drought necessitated drastic demand management.; We assessed consumer behaviour change with time-of-day and day-of-the-week analysis of household water usage.; The first big reduction was due to residents reducing usage in the early morning and evening on weekdays.; The second occurred in the mid-morning on weekdays when residents were not at home but ensured their domestic workers reduced their usage.;